Suppression of endurance degradation by applying constant voltage stress in one-transistor and one-resistor resistive random access memory. (28th November 2016) - Su, Yu-Ting; Chang, Ting-Chang; Tsai, Tsung-Ming; Chang, Kuan-Chang; Chu, Tian-Jian; Chen, Hsin-Lu; Chen, Min-Chen; Yang, Chih-Cheng; Huang, Hui-Chun; Lo, Ikai; Zheng, Jin-Cheng; Sze, Simon M.
Abstract: In this letter we demonstrate an operation method that effectively suppresses endurance degradation. After many operations, the off-state of resistance random access memory (RRAM) degrades. This degradation is caused by reduction of active oxygen ions participating in the set process, as determined by current fitting of current–voltage ( I – V ) curves obtained from the endurance test between the interval of seventy to one hundred million operations. To address this problem, we propose the application of constant voltage stress after every five million operations during the endurance test. The experimental result shows that this method can maintain oxygen ions at the proper depth in the electrode and improve RRAM reliability.